High-gain low-profile circularly polarized patch antenna for universal RFID reader application. Issue 2 (22nd January 2022) - Zhou, Qilei; Fu, Guang; Sun, Chao
Abstract : It is known that for a microstrip antenna, if the height of the antenna is strictly limited, then the bandwidth is narrow. A way to solve this problem is to combine two modes. However, for almost all the two-mode resonant patch antennas reported, the height of the antenna conflicts with the frequency ratio of the two modes. The smaller the frequency ratio is, the higher the antenna. In this paper, a detailed mode analysis is performed, and a comprehensive mode shift design method is established. A dual resonant patch antenna with any frequency ratio can be designed. Guided by this method, a low-profile wideband patch antenna with a size of only 0.6λ0 × 0.6λ0 × 0.05λ0 for the universal RFID reader (840-960 MHz) is designed. The simulated and measured results show that a low-profile is achieved for universal RFID reader antennas.